EFEKTIVITAS KONSELING KELOMPOK DENGAN TEKNIK SELF MANAGEMENT UNTUK MENGURANGI KECANDUAN GAME ONLINE PADA SISWA - Putri Fazillah; Teuku Fadhli; Muqarramah Fitri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2022)
This study aims to determine whether the implementation of group counseling with self-management techniques is effective in reducing online game addiction of SMAN 1 Sakti students. The method used in this study is a quasi-experimental design with The Nonequivalent Control Group 3Design. The population in this study were 42 students. The sample was taken by purposive sampling technique with a sample of students of class XI IPA1 and XI IPA2. Data was collected by means of a questionnaire or questionnaire. The data was processed using SPSS version 20 for windows. The results showed that there was effectiveness in implementing group counseling with self-management techniques to reduce online game addiction in class XI Mipa 1 and XI Mipa 2 SMA Negeri 1 Sakti. This is evident from the posttest with the self-management technique tcount t table, then -13.53 2.01, this minus sign means the direction is getting smaller or the area of H0 acceptance is on the left. Self-management techniques that are able to reduce (reduce) online game addiction in students. Then Ha is accepted and H0 is rejected. The independent sample-t test showed that there was a difference between the experimental and control classes. This difference can be in the form of the effectiveness of self-management counseling techniques in reducing online game addiction in students at SMA Negeri 1 Sakti.Keywords: Group Counseling Services_Self Management Techniques_Online Game Addiction.